Aspalathus and Podalyria legumes balance acquisition of phosphorus and nitrogen for growth in nutrient poor fynbos soils - Maistry, Pravin Mark (Department of Biological Sciences, 2015)
Legume species nodulate and grow successfully in the Core Cape Subregion, a Mediterranean-climate ecosystem with fynbos vegetation found on infertile soils. The physiological mechanisms enabling tolerance of low availability of phosphorus (P) are yet to be reported in Cape legume species such as Aspalathus linearis and Podalyria calyptrata; species that demonstrated traits typical of plants from nutrient poor soils. In the three research chapters of the thesis, it was anticipated that low P supply would limit plant growth and increase expression of traits for P acquisition.